The impact of innovation policy and the bureaucratic structure reform of organizational citizenship behavior (OCB) of the government agencies in Padang city, Indonesia - Zulfia, Haira; Syamsir, Syamsir (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
This study purpose to investigate and analyze the influence of innovation policy and bureaucratic structure reform on organizational citizenship behavior (OCB) of apparatuses in the government agencies in Padang City. In this study, innovation policy and bureaucratic structure reform were the independent variables and OCB was the dependent variable. The population of this study was apparatuses at several the government agencies in Padang City with a total of 30 people. Data collection techniques were collected through questionnaires and literature study. Hypothesis testing done by using statistical tests, especially multiple regression analysis. The feasibility test of the model was obtained from the adjusted R-squared value of .0524 which means that up to 52.4% of variations in apparatus OCB can be explained by testing the variations of two independent variables, namely innovation policy and bureaucratic structure reform. While the remaining 47.6% was explained outside the model. The results of the causality test obtained by looking at the influence of innovation policy and reform of the bureaucratic structure on the OCB variable with a reliability level of 99%. From this study, it can be concluded that the innovation policy and bureaucratic structure reform variables had a significant effect toward the OCB of apparatuses in the government agencies in Padang city.